The Tilawah dan Qira’ah Upaya Untuk Meningkatkan Pemahaman dan Praktik Membaca Al-Qur’an - Sheleisya, Adinda Hasna; Suharman, Cucu; Sumarna, Elan (Arfannur: Journal of Islamic Education, 2025)
Al-Qur'an education plays an important role in forming character, increasing knowledge and religious skills of children. The aim of this research is to examine the application of the concepts of recitation and qira'ah in Al-Qur'an education as an effort to improve understanding and practice of reading the Al-Qur'an. The problem raised is how Al-Qur'an education can guide children to read fluently, correctly, and understand the meaning contained in it. The method used is a literature study by examining various relevant sources regarding the theory and practice of recitations and qira'ah in Islamic education. The results of this research show that recitations and qira'ah are not just reading skills, but also a means to understand and practice the teachings of the Qur'an in everyday life. Learning that involves both can develop good social behavior, strengthen character, and increase children's closeness to Islamic teachings. In this way, it is hoped that Al-Qur'an education will be able to produce a generation that is not only skilled at reading, but also has noble morals.